Kepentingan Ekonomi Politik Indonesia dalam Kerjasama Comprehensive Economic Partnership Agreement dengan Australia - Bahjatul Murtasidin (T JDP (JURNAL DINAMIKA PEMERINTAHAN), 2021)
The dynamics of the diplomatic relations between Indonesia and Australia which was followed by a trade balance deficit prompted Indonesia to take the initiative to strengthen a comprehensive economic partnership. This is also in line with one of the policy priorities of the President and Vice President of the Republic of Indonesia for the 2014-2019 period, namely strengthening the economic sector. Therefore, the Government of Indonesia's economic diplomacy efforts are carried out through trade facilitation through trade agreements with partner countries. The Indonesia-Australia Comprehensive Economic Partnership Agreement (IA-CEPA) is a cooperation agreement scheme that aims to increase trade and investment between the two countries, integrate both bilateral economies, and form a solid foundation in various areas of cooperation. This research uses national interest theory with descriptive analysis method. The results of this study indicate that the IA-CEPA cooperation is used as a means to strengthen bilateral relations as well as efforts to achieve economic interests so that they no longer experience a trade balance deficit.